Caciotta della Garfagnana cheese: selection and evaluation of autochthonous mesophilic lactic acid bacteria as starter cultures - Barbara Turchi; Roberta Nuvoloni; Filippo Fratini; Francesca Pedonese; Valentina V. Ebani; Domenico Cerri (Italian Journal of Animal Science, 2011)
he aim of this study was to isolate, identify and select, with respect to acidification and proteolytic activities, the autochthonous mesophilic lactic acid bacteria (LAB) present in milk and Caciotta della Garfagnana, a cheese produced either with raw or thermised cow’s milk in small dairies and family plants of Garfagnana (Tuscany), to obtain LAB strains with attributes suitable to be employed as starter cultures in this type of cheese, particularly when thermised milk is used to control spoilage microflora. Samples of raw milk, curd and cheese were collected from three representative farmers of the production area and used to isolate autochthonous LAB. Phenotypic and genotypic (species-specific PCR assay) identification of isolated LAB was done. Twenty-eight strains of LAB isolated from milk, curd and cheese were screened for acidifying and proteolytic activities. LAB strains with the better attributes were used as mesophilic starter cultures in technological trials: experimental cheeses manufactured with the addition of autochthonous LAB and control cheeses were compared for LAB and pH evolution. Experimental cheeses presented a significant increase in the mesophilic lactic acid microflora up to 14 days of ripening and significantly lower pH values up to seven days of ripening. The use of wild selected mesophilic lactic acid bacteria, together with thermisation of milk, for the Caciotta della Garfagnana looks very promising and could help to both standardise the production and improve quality and traditional characteristics of this type of cheese.